MEANING RELATIONS AND SEMANTIC INTERPRETATION IN THE DIALOGUES OF THE FILM SORE (2025) - Indah Sari Ramadhani; Zauti Maula; Safety Mahadika Putri Assaidi; Tatu Siti Rohbiah (Jurnal Ikhtibar Nusantara, 2026)
This study analyzes meaning relations and semantic interpretations in the dialogues of the film Sore (2025) from a semantic perspective. The aims of this research are to identify the types of meaning relations found in the film dialogues and to explain how utterance context influences semantic interpretation. This study employed a qualitative method with a descriptive approach. The data were collected through observation and note-taking techniques from dialogues spoken by the main characters in the film. The findings reveal three types of meaning relations, namely associative meaning, polysemy, and antonymy. Associative meaning becomes the most dominant type with 13 data, followed by polysemy with 7 data and antonymy with 5 data. In addition, the semantic interpretations identified in the dialogues include contextual, connotative, emotional, and referential interpretations. Contextual interpretation is the most dominant with 19 data, while connotative and emotional interpretations each appear in 5 data, and referential interpretation appears in 1 data. These findings indicate that the meanings in the film dialogues are strongly influenced by conversational situations, emotional conditions, relationships between characters, and implied meanings. Therefore, understanding the dialogues in the film requires not only literal interpretation but also contextual and emotional understanding in order to comprehend the intended meanings accurately.